Analysis and discovery of procrastination patterns in a language learning MOOC - Vázquez Mendoza, Jorge A.; Ramírez, Cèsar Ferri; Aranda, Carlos Monserrat (Computers and education, 2024)
Online learning has been gaining a broad notoriety in society in the last years. The ease with which users from all over the world can learn is one of its main attractions. MOOCs are one of these technologies, which have enabled users to learn almost any subject of their interest. The use of MOOCs generates a massive amount of data that has been used by researchers with different goals: to predict dropout, predict grades and determine learning styles. Users of MOOCs face several challenges, some of which have been extensively studied. However, there are some of them, such as procrastination, whose study as a determining factor in the failure of such courses has not been addressed in sufficient depth. Through this paper, the influence of procrastination on the failure rates of users in a MOOC has been uncovered. Furthermore, by using process mining, this research has revealed the existence of a pattern of procrastination and the type of material used during study sessions by the users who fail the course. Speclifically, diverse forms of procrastination have been identified, resulting in differing effects on the educational outcomes attained by the user. These findings possess considerable implications, as they underscore the potential worth of detecting specific procrastination patterns to ascertain users who necessitate supplementary support during their educational pursuits within MOOCs. •Process mining is very useful for identifying behavioral patterns in virtual environments.•Procrastination is a learning challenge in virtual environments that can be crucial in the success and/or failure of a user.•The procrastination time intervals within a study session are more relevant than the period that elapses between sessions.•In a MOOC language course, the interactivity of the study material plays a fundamental role in keeping the user's attention.•It is necessary to expand the application of Comput. Sci. Tech. in the análisis of procrastination in virtual environments.